2009
DOI: 10.1007/s11218-009-9104-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between parental involvement, self-regulated learning, and reading achievement of fifth graders: a path analysis using the ECLS-K database

Abstract: This study examined the relationship between parental involvement, selfregulated learning (SRL), and reading achievement through analyzing the fifth grade data from the Early Childhood Longitudinal Study, Kindergarten Class of 1998-1999 (ECLS-K). The results identified six dimensions of parental involvement that are likely to foster SRL of fifth graders: School Involvement, TV Rules, Homework Help, Homework Frequency, Parental Education Expectations, and Extracurricular Activities. Of these three dimensions, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
3
19

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 55 publications
(67 reference statements)
3
62
3
19
Order By: Relevance
“…No effect was found for home-based involvement; however, in-depth analyses that examined different types of home-based involvement revealed that parental homework involvement was the only aspect that showed a negative association and thus cancelled out the positive effects of other activities at home. Based on these meta-analyses as well as on more recent studies (Fan & Williams, 2010;Karbach et al, 2013;M€ agi, Lerkkanen, Poikkeus, Rasku-Puttonenn, & Nurmi, 2011;Xu et al, 2010;You & Nguyen, 2011), it can be concluded that parental involvement has an effect on students' academic achievement. However, because the meta-analyses used different methods to combine the results and to calculate the effect sizes, it is hard to draw more specific conclusions.…”
Section: Previous Studies On the Effectiveness Of Parental Involvementmentioning
confidence: 91%
“…No effect was found for home-based involvement; however, in-depth analyses that examined different types of home-based involvement revealed that parental homework involvement was the only aspect that showed a negative association and thus cancelled out the positive effects of other activities at home. Based on these meta-analyses as well as on more recent studies (Fan & Williams, 2010;Karbach et al, 2013;M€ agi, Lerkkanen, Poikkeus, Rasku-Puttonenn, & Nurmi, 2011;Xu et al, 2010;You & Nguyen, 2011), it can be concluded that parental involvement has an effect on students' academic achievement. However, because the meta-analyses used different methods to combine the results and to calculate the effect sizes, it is hard to draw more specific conclusions.…”
Section: Previous Studies On the Effectiveness Of Parental Involvementmentioning
confidence: 91%
“…This supports previous research that advocated the importance of parents in students' learning (e.g. Midraj & Midraj, 2011;Walker, et al, 2005;Xu, et al, 2010). The implication of activity theory in this study is that community provides an important role in achieving the object of an activity system.…”
Section: Mra/gi) He Said 'Not Easy For Me To Ask For Help To My Parsupporting
confidence: 90%
“…Com influências de paradigmas construtivistas, que tem o indivíduo como agente de seu aprendizado (Arias et al, 1999;Xu et al,2010;Richter & Schmid, 2010), Zimmerman (2001) aborda que os indivíduos são considerados autorregulados quando são persistentes, decididos, estratégicos e capazes de avaliar seus progressos; aqueles que são mais dependentes cognitivamente são, portanto, pouco autorregulados. Para Ribeiro (2003), a realização de autocrítica, a reflexão pessoal, a capacidade de realização da autocrítica, a modificação de hábitos de estudos são características de estratégias metacognitivas.…”
Section: Autorregulação Da Aprendizagemunclassified
“…Outros estudos apontam existir diferenças significativas entre aluno autorregulado e outros que precisam de regulação externa no aprendizado (Arias, Barca Lozano, Gonzalez Cabanach, & Núñez Pérez, 1999;Xu, Benson, Mudrey-Camino, & Steiner, 2010;Richter & Schmid, 2010). Indivíduos autorregulados são decididos, adotam estratégias, são persistentes e avaliam seus progressos; diferente daqueles que não traçam objetivos educacionais e consequentemente possuem dependência cognitiva, assim, pouca autorregulação na aprendizagem (Zimmerman, 2001).…”
Section: Introductionunclassified